Mind-wandering and its Relationship to Academic Engagement among Umm Al-Qura University Students - Al-Huthale, Taghreed Daefallah; Al-Harbi, Nawar Mohammad Saad (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the nature of the relationship between mind- wandering and academic engagement. The study sample consisted of 420 undergraduate students majoring in science and humanities who were selected using the stratified random sampling method. The mind- wandering scale prepared by Elfiel (2018) and the academic engagement scale prepared by Mahasneh et al. (2019) were applied, and the descriptive- correlative approach was also used. The results of the study revealed that the students of Umm Al-Qura University are characterized by a high level of mind- wandering and academic engagement. There was a statistically significant relationship between mind- wandering and academic engagement. The study recommended training students on some exercises that may help reduce mind- wandering and raise the level of focus and attention during tasks, such as mindfulness exercises. The study also stressed the importance of discovering the academic and social problems facing university students and activating the role of academic counseling in order to help them solve these problems in order to increase academic engagement.
Keywords: Mind-wandering; Academic Engagement; Umm Al-Qura University students